Functional characterization of two 3-dehydroquinases of AroQ1 and AroQ2 in the shikimate pathway and expression of genes for the type III secretion system in Ralstonia solanacearum - Zhang, Qingshan; Wu, Bofan; Han, Liangliang; Yu, Duan; Liang, Tao; Wang, Yan; Guo, Tao (Frontiers in Microbiology, 2023)
Shikimate pathway is a general route for biosynthesis of aromatic amino acids (AAA) in many microorganisms. 3-dehydroquinase, AroQ controls the third step of shikimate pathway that catalyzes formation of 3-dehydroquinate from 3-dehydroshikimate via a trans-dehydration reaction. Ralstonia solanacearum harbors two 3-dehydroquinases, AroQ1 and AroQ2, sharing 52% similarity on amino acids. Here, we demonstrated that two 3-dehydroquinase, AroQ1 and AroQ2 are essential for shikimate pathway in R. solanacearum. Growth of R. solanacearum in a limited medium and pathogenicity on host plants was diminished with deletion of both aroQ1 and aroQ2, but no alteration in mutants with deletion of either gene. The aroQ1/2 double mutant could thrive in host plants but grew slowly, which was about four order of magnitude less than the parent strain to proliferate to the maximum cell densities in tomato xylem vessels. Supplementary shikimic acid (SA), an important intermediate of shikimate pathway, substantially restored the diminished growth of double mutant in limited medium and inside host plants. Necessity of AroQ1 and AroQ2 on pathogenicity of solanacearum toward host plants was partially due to insufficient SA inside host plants. Moreover, deletion of both aroQ1 and aroQ2 significantly impaired expression of genes for type three secretion system (T3SS) both in vitro and in planta. Its involvement on the T3SS was mediated through the well-characterized PrhA signaling cascade and was independent of growth deficiency under nutrient limited conditions. Taken together, R. solanacearum 3-dehydroquinases play important roles on bacterial growth, expression of the T3SS and pathogenicity in host plants. These results could extend our insights into understanding of biological function of AroQ and sophisticated regulation on the T3SS in R. solanacearum.